Determining the Quality of English Teacher-Made Test: How Excellent is Excellent? - Nurhalimah Nurhalimah; Fahriany Fahriany; Dadan Dadan (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
Many studies have been conducted on evaluating the quality of a teacher-made test. Item analysis is crucial for making a good test, and improving test items. In response to the advantages of item analysis, this study looks at the theoretical and practical benefits of item analysis. The objectives were to know and to describe the extent of the quality of the English test items concerning difficulty level and discriminating power. This research used descriptive quantitative analysis. A total of 171 respondents of second-year students at MAN 1 Kota Tangerang Selatan 2017/2018 academic year were included in this study. The findings indicate that the English mid-term test has 24 acceptable items (80%) from the quality excellent, good, and satisfactory. Then, three items (10%) have poor quality, and three items (10%) have very poor quality, or in the negative value on discrimination index to the extent that the items are eliminated. It is proven by statistical data that they fail to distinguish between students who are knowledgeable and those students who are not on the base of how well they know the materials that have been tested.